Carbon-dots from babassu coconut (Orbignya speciosa) biomass: Synthesis, characterization, and toxicity to Daphnia magna - Rubens S. Costa (Elsevier, 2021)
The present study provides amethodology for the synthesis of carbon dots through hydrothermal carbonization of the babassu coconut (Orbignya speciosa) mesocarp as a precursor matrix. The synthesis parameters (temperature, residence time and% m/v) were studied through a factorial design with the fluorescence intensity as determining factor in choosing the best sample. Particles with diameters in the range of 2.4 - 47.7 nm were obtained, which presented two emission regions, one at approximately 467 nm (λEX = 370 nm) and the other at approximately 550 nm (λEX = 470 nm). These carbon dots showed the phenomenon of suppression of fluorescence when in the presence of Fe3+, Co2+, Ni2+, Zn2+, Cu2+ and Cd2+ ions, exhibiting good linearity in the fluorescence decay according to the concentration of ions in the medium, indicating potential application as a sensor for these ionic species. Acute toxicity testing with Daphnia magna model demonstrated absence of toxic effect (immobility) of the carbon dots to this aquatic organism bioindicator after 48 h of exposure, even at high concentrations (up to 1000 mg.L−1).